2017
DOI: 10.1108/cms-12-2016-0263
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and turnover intention in China

Abstract: Purpose This paper aims to examine the moderating effects of job alternatives and policy support on the relationship between job satisfaction and turnover intention. Design/methodology/approach A questionnaire survey was conducted in China. The study sample consisted of employees from organizations of different sizes, ownerships and industry types. Finally, 462 valid questionnaires were obtained. Findings Cognitive job satisfaction has a stronger negative effect on turnover than affective job satisfaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 69 publications
(125 reference statements)
2
11
0
1
Order By: Relevance
“…Many factors make employees dissatisfied in organisations. This dissatisfaction causes intention to leave the job (Huang et al., 2017), and employees leave their job at the end of this process. To theorise how employees depart, Mobley’s (1977) seminal model posits that dissatisfaction → thought of quitting → subjective expected utility analysis of the benefits and costs of seeking alternative jobs → search intentions → evaluation of alternative job offers → comparison of job offers with the present job → intention to quit (after choosing a job offer) → actual quitting (Lee et al., 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many factors make employees dissatisfied in organisations. This dissatisfaction causes intention to leave the job (Huang et al., 2017), and employees leave their job at the end of this process. To theorise how employees depart, Mobley’s (1977) seminal model posits that dissatisfaction → thought of quitting → subjective expected utility analysis of the benefits and costs of seeking alternative jobs → search intentions → evaluation of alternative job offers → comparison of job offers with the present job → intention to quit (after choosing a job offer) → actual quitting (Lee et al., 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Dalam hasil pengujian H4 yang menunjukan bahwa ditolaknya job satisfaction tidak berpengaruh secara langsung dan signifikan terhadap turnover intention pada karyawan PT XYZ, maka hal ini tidak sesuai dengan penelitian yang dilakukan oleh Hasil penelitian yang dilakukan oleh Huang et al (2017) menyatakan bahwa job satisfaction memiliki hubungan yang signifikan negatif terhadap turnover intention. Dengan ditolaknya H4, maka semakin tinggi job satisfaction maka akan semakin rendah turnover intention meskipun tidak signifikan.…”
Section: Pembahasanunclassified
“…The data revealed that the choice of task and task performance has positive impact on employee turnover and data shows that there should balance in order to attract potential employee that affect task satisfaction that directly led to turnover. Similar study was conducted by (Huang, 2017)a questionnaire was developed to gather data in China, the sample of the study consisted of employees from different size, organization and industries and distributed 462 questionnaires among them. The result showed that task satisfaction has negative influence on turnover intention.…”
Section: Task Satisfactionmentioning
confidence: 99%